KEAWETAN PAPAN PARTIKEL BATANG KELAPA SAWIT DARI PROSES PERENDAMAN PARTIKEL YANG BERBEDA TERHADAP RAYAP TANAH COPTOTERMES CURVIGNATHUS HOLMGREN - Saman, Abdus; Diba, Farah; Setyawati, Dina; haida, Nur (Universitas Tanjungpura, 2016)
Oil palm trunk became a huge waste when the oil palm reached twenty fifth years old. This unproductive oil palm will replant with a new oil palm tree. Meanwhile the trunk was a big source of cellulose which can be used as particleboard. Research aimed to evaluate the durability of particleboard made from oil palm trunk against subterranean termites Coptotermes curvignathus Holmgren. This research was conducted in Laboratory of Wood Technology in Forestry Faculty Tanjungpura University, Pontianak, West Kalimantan, Indonesia. The treatment of particle of oil palm trunk was dipping in hot water for two hours, dipping in cold water for seven hours and dipping in NaOH 5%for two hours.Each treatment was made in fifth replication. Durability test against subterranean termites was conducted with force feeding test. Sample was measured 2 cm x 2 cm x 1 cm and put in glass with fifty termites (45 workers and 5 soldiers) then keep in culture room for 21 days. The weight loss of particleboard sample and mortality of termites was count for measured the durability of particleboard. Result of research showed that the highest average value of weight loss of oil palm particleboard was on treatment particle dipping in cold water for seven hours, then particle dipping in hot water and NaOH5% (2.75%; 0.65% and 0.23% respectively). Mortality of termites reaches 100% on particleboard made from dipping in NaOH5%. It is concluded that the durability of oil palm particleboard made from dipping particle in NaOH was the highest than other treatment. Keywords:Coptotermes curvignathus, dipping, durability, oil palm trunk, particleboard